Analysis of The Meaning of Comparison and Contrast Figures in the Song Shiawase Album Love Story by Back Number - Rike Widia Dinanda; Ayu Putri Seruni (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This research analyzes the figures of speech, specifically comparison and contrast, in the song "Shiawase" from the Love Story album by Back Number. Through qualitative methods, the study identifies how these figures enrich the emotional depth of the lyrics, depicting the inner conflict of unrequited love. The analysis reveals that comparative expressions highlight the character "I"'s feelings of inferiority, emotional vulnerability, and selfless sacrifice, while oppositional figures illustrate the tension between desire and reality. The findings indicate that figurative language serves not only to enhance aesthetic value but also to convey profound emotional messages, emphasizing the theme of hidden love and the nobility of prioritizing another's happiness. This study contributes to the understanding of stylistic analysis in Japanese popular music, filling a gap in the literature regarding cross-cultural literary studies